Sistematización de la experiencia del rediseño del procedimiento de subsidio por enfermedad y su impacto en la dinámica organizacional en la Empresa EP Petroecuador, en el período septiembre 2016 a agosto 2017 - Riera Guillen, Franklin Alberto (2018)
The systematization compiles the practical experience of the project "Redesign of the procedure of subsidy for illness and its impact in the organizational dynamics", which was developed in the Payroll Department of the EP Petroecuador company. All the information was gathered and developed in a qualitative manner, detailing in a critical and reflective way the acquired experiences making possible the elaboration of a project that helped the Payroll Department at EP Petroecuador company by redesigning the subsidy procedure for illness. The previous procedures were not adapted to business requirements; therefore, a need for these to be redesigned was observed in order for it to continue operating as it was paralyzed. This project was supported by the company and other external institutions such as the IESS that provided all the necessary information for this systematization. The project emphasizes the learning that arises around the stages of the new subsidy procedure for illness, and the impact generated in the business dynamics at the structural, economic and psychosocial levels.